(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author describes the ’Heroine’s House’ on St Kilda including its dimensions and construction. He notes its similarities to other ’beehive houses’ found in the Outer Hebrides. Also included in this article is a letter sent to the author from Captain F W L Thomas about a legend associated with this part of St Kilda.